4CPS-378 Oral therapy adherence and satisfaction in patients with multiple myeloma. (14th March 2021) - Solano, M; Faure, C; Pain, C; Loriod, P; Maes, AC; Marguet, P; Kroemer, M; Rumpler, A; Daguindau, E; Limat, S; Clairet, AL
Abstract : Background and importance: The transition to oral therapies in patients with multiple myeloma (MM) offers potential benefits to patients, however they must self-manage their medications and adherence can become an issue. It has been shown that patient satisfaction with medication has a strong positive correlation with adherence in chronic diseases. To date, there is no standard method of measuring adherence. Aim and objectives: The aim of this study was to estimate the adherence rate of oral antimyeloma therapies using two indirect methods and to identify risk factors for medication non-adherence. A secondary aim was to explore patients' and caregivers' perceptions of their medications. Material and methods: We carried out a cross sectional, observational, prospective, multicentre survey based on a self-reported questionnaire. All consecutive MM patients, with at least 3 months of oral therapy prescriptions were included. The structured and validated 6 item Girerd Scale and the medication possession ratio (MPR) were used for measuring medication adherence, and the SATMED-Q questionnaire was used for measuring patient satisfaction with the medication. An analysis of risk factors for non-adherence to oral therapy was performed using univariate analysis. Patients' and caregivers' opinions about their medications were assessed with a score from 0 (no importance) to 10 (highest importance). Results: 101 of 116 analysed patients participated in the survey, giving a response rate of 87%. The prevalence of adherence to oral antimyeloma therapy was estimated at 51.5% using the questionnaire, corresponding to a high level of adherence (ie, score=6). According to the MPR, adherence was evaluated at 96%, which was also considered high (ie, MPR ≥0.80). With both methods combined, adherence was estimated at 50.5%. One risk factor for non-adherence to oral antimyeloma therapy was identified: Eastern Cooperative Oncology Group Performance Status (ECOG-PS) >2 (p value=0.007). One predictive factor for good adherence to oral antimyeloma therapy was also identified: high satisfaction with treatment (p=0.01). No statistically significant difference was observed between patients and caregivers' perceptions of their medications. Conclusion and relevance: Determining risk factors that influence adherence could be helpful to better identify patients at a higher risk for non-adherence, to personalise therapeutic information and education, and to improve the quality of healthcare overall. References and/or acknowledgements: Conflict of interest: No conflict of interest